2019
DOI: 10.4062/biomolther.2019.074
|View full text |Cite
|
Sign up to set email alerts
|

A New Histone Deacetylase Inhibitor, MHY4381, Induces Apoptosis via Generation of Reactive Oxygen Species in Human Prostate Cancer Cells

Abstract: Prostate cancer is the most common type of cancer diagnosed in men. In 2018, prostate cancer represented 19% of all cancer diagnoses in men in the United States, which is the highest in the entire world (Siegel et al., 2018). The current front-line therapies for prostate cancer are either surgical removal of the tumor or radiation therapy, regardless of androgen sensitivity (Balk and Knudsen, 2008; Schröder et al., 2012). The androgen receptor (AR) is a transcription factor that plays a pivotal role in the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…However, the question remains as to whether the increased intracellular iron levels proceed ROS accumulation during EMT, or if high levels of ROS are disrupting Fe–S cluster synthesis to increase IRP mRNA binding to ultimately promote mesenchymal cell iron accumulation. Moreover, because both HDAC inhibitor treatment and alterations in cellular iron availability can promote apoptosis, which in turn can elicit ROS generation in mitochondria [ 26 , 28 , 29 ], future studies should seek to mechanistically determine how HDAC inhibitor treatment augments cell death following ferroptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the question remains as to whether the increased intracellular iron levels proceed ROS accumulation during EMT, or if high levels of ROS are disrupting Fe–S cluster synthesis to increase IRP mRNA binding to ultimately promote mesenchymal cell iron accumulation. Moreover, because both HDAC inhibitor treatment and alterations in cellular iron availability can promote apoptosis, which in turn can elicit ROS generation in mitochondria [ 26 , 28 , 29 ], future studies should seek to mechanistically determine how HDAC inhibitor treatment augments cell death following ferroptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that abrogation of apoptosome-mediated caspase activation and defective release of Cyt c from the mitochondria are associated with prostate cancer aggressiveness observed in African American men [ 62 ], further supporting an important role of Cyt c as a cancer driver. Other studies have shown that acetyltransferases mediating protein acetylation are upregulated in prostate cancer [ 63 , 64 ] and could be established as rational therapeutic targets [ 65 , 66 ]. Therefore, a better mechanistic understanding of Cyt c acetylation in prostate cancer and potentially other cancers may allow the development of novel effective cancer therapeutics that target Cyt c for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Cells that show clear synergistic cell death upon treatment with auranofin and R428, such as the MDA-MB-231, MCF-7, PC-3, and Hep3B cells, are known to have low levels of NRF2 activity. In contrast, the HeLa and H520 cells have relatively higher NRF2 activity ( Zhang et al ., 2010 ; Cazanave et al ., 2014 ; Mine et al ., 2014 ; Lu et al ., 2017 ; Richa et al ., 2020 ). Since the synergistic effect of auranofin and R428 is expected to enhance ROS production, it is presumed that the effect of the combination treatment might be weak in the NRF2-activated cancer cells.…”
Section: Discussionmentioning
confidence: 99%